Identifikasi Efedrin dan Pseudoefedrin Sediaan Padat dengan Metode Ultra Performance Liquid Chromatography dan High Performance Liquid Chromatography - Ichsan, Dewi Susetiyany; Ebtasari , Ma'rifah (Eruditio : Indonesia Journal of Food and Drug Safety, 2023)
Ultra Performance Liquid Chromatography (UPLC) is an analytical separation that maintains the practicality and principles of High-Performance Liquid Chromatography (HPLC) by increasing analysis speed, sensitivity, and resolution. The methods used for the identification of ephedrine and pseudoephedrine have been carried out using HPLC according to MA PPOMN 07/NA/2010 from the National Quality Laboratory of Drug and Food (NQCLDF). The aim of the study was to assess the superiority of the UPLC method compared to HPLC in the evaluation of ephedrine and pseudoephedrine solid dosage forms. UPLC used UPLC Waters with PDA detector at wavelength 210 nm, Aqquity column UPLC® BEH C18 (50 x 2.1 mm) with particle size 1.7 μm, mobile phase of sodium lauryl sulfate solution 25 mM and acetonitrile (60:40), flow rate 0.3 ml/min, injection volume 1 μL. Comparative parameters used in the validation of ephedrine and pseudoephedrine compounds by UPLC and HPLC methods are specificity and selectivity. The validation of the UPLC method shows the retention time for ephedrine and pseudoephedrine at minutes 3,288 and 3,048 with an RSD retention time of 0.3% and an area of 0.5%. The resolution between ephedrine and pseudoephedrine was 1.9. The length of analysis time is 27 minutes on HPLC and 6 minutes on UPLC. Based on the results of this study, the UPLC method can be used as an alternative to determine ephedrine and pseudoephedrine in solid preparations with the advantages of faster, better resolution, fewer mobile phase, reference standard and samples and shorter workload than HPLC